Prevalence of headache and impact on anxiety in adults - Febriannie, Angela; Sanusi, Renobulan; Fahdiyani, Reny; Dwianasari, Riani (Universa Medicina, 2010)
Headache is an extremely common symptom that may have profound impact on peoplesâ functioning and quality of life. The two most common primary headache disorders, migraine and tension-type headache, have an annual prevalence of respectively 11% and 40% in adults. The objective of this study was to estimate the prevalences of headache and anxiety in primary care patients and the impact of headache on anxiety in these patients. A cross-sectional study was conducted on 140 adult patients attending a primary health center. Outcome measures included headache impact test scores and Zung-self rating anxiety scale. The mean age of the respondents was 34.6 Â± 5.2 years (range 22 - 44 years). Sixty one respondents (43.6%) in the preceding month had suffered from headaches that affected their lives, and 91 respondents (65.0%) had anxiety symptoms and a raw anxiety score of more than 40. There was a significant association between headaches affecting the lives of the respondents and the anxiety resulting from the headache (p=.0001). Among 16 respondents with attacks of headaches that severely affected their lives, 87.5% were disturbed by anxiety. In conclusion, there was a relatively high proportion of patients in the primary care setting experiencing headaches that potentially affected their lives and had an impact on their anxiety. It may be appropriate to encourage patients to inform their health-care providers about their headaches and to encourage providers to identify patients with frequent headaches.